2015
DOI: 10.1007/s10552-015-0679-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination and cancer screening behaviors in US Hispanics: the Hispanic Community Health Study/Study of Latinos Sociocultural Ancillary Study

Abstract: Purpose Perceived discrimination has been associated with lower adherence to cancer screening guidelines. We examined whether perceived discrimination was associated with adherence to breast, cervical, colorectal, and prostate cancer screening guidelines in US Hispanic/Latino adults. Methods Data were obtained from the Hispanic Community Health Study/Study of Latinos Sociocultural Ancillary Study, including 5,313 Hispanic adults ages 18–74 from Bronx NY, Chicago IL, Miami FL, and San Diego CA who were within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…One exception was Cheng and Mallinckrodt (2015), who used a longitudinal design with a 1-year follow-up period. Nationally representative cohort studies with probability sampling were the primary source of data in this category (Ornelas & Hong, 2012; Otiniano Verissimo, Gee, et al, 2014; Otiniano Verissimo, Grella, et al, 2014; Valdovinos et al, 2016). Latino ethnic background and nativity were reported consistently, expect in Nguyen et al (2012).…”
Section: Resultsmentioning
confidence: 99%
“…One exception was Cheng and Mallinckrodt (2015), who used a longitudinal design with a 1-year follow-up period. Nationally representative cohort studies with probability sampling were the primary source of data in this category (Ornelas & Hong, 2012; Otiniano Verissimo, Gee, et al, 2014; Otiniano Verissimo, Grella, et al, 2014; Valdovinos et al, 2016). Latino ethnic background and nativity were reported consistently, expect in Nguyen et al (2012).…”
Section: Resultsmentioning
confidence: 99%
“…The quality of patient-centered communication has implications for patient health and psychosocial outcomes including quality of life, adherence to cancer screening guidelines, and satisfaction. 12,13,36,37 Lower levels of patient-centered communication as indicated by the lack of clarity, perceived discrimination, and disrespectful office staff domains on the IPC were associated with lower quality of life in a cohort of breast cancer survivors. 12 Higher perceived discrimination among Hispanic/Latino men has been associated with lower adherence to cancer screening guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…12 Higher perceived discrimination among Hispanic/Latino men has been associated with lower adherence to cancer screening guidelines. 13 In a study among an ethnic and racially diverse group of adults aged 50 and older, the perceived interpersonal sensitivity of the provider seen most recently in the past year was positively associated with satisfaction with health care. 36 A study of the association of patient perceptions of communication by health care providers with patient language (English v. Spanish) and ethnicity (Latino v. white) found that Spanish-speaking and Latino patients were less satisfied than English-speaking and white patients with how well medical staff listened, answered their questions, explained medications, explained medical procedures and tests results, and provided reassurance and support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Other factors, such as low educational attainment, lack of insurance, and no usual source of health care, 36 which are common among Hispanics, are also associated with CRC screening. 31,37 There may also be differences in cultural and health beliefs contributing to screening, for example, Hispanics frequently report medical mistrust. 38 Slower declines in CRC incidence, combined with low screening uptake, underscore the importance of screening outreach interventions targeted to Hispanic populations, such as those in community health centers 3941 and safety-net systems.…”
Section: Discussionmentioning
confidence: 99%